(untitled) (KULT_online, 2015)
The economist William Easterly continues to challenge development work. His survey puts an emphasis on the dominance of a technocratic approach in the fight against global poverty. In doing so he compares it to diverging views through a historic, political, and economic analysis. Authoritarian development comprises the experts’ and governments’ search for technical solution strategies. Free development, though, bonds a personal-rights consolidation and spontaneous decision-making by individuals. Both ideas were imagined to pave the way out of poverty. But it was the first that has gained acceptance since World War I and still applies today. The author questions the success of the authoritarian idea after 65 years of fighting against poverty and demands a debate on the "technocratic illusion". His new book, The Tyranny of Experts. Economists, Dictators and the forgotten Rights of the Poor, marks its beginning.